2020
DOI: 10.1155/2020/6947839
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of the WeChat App Combined with Pelvic Floor Muscle Exercise for the Urinary Incontinence after Radical Prostatectomy

Abstract: Objective. This research is aimed at studying the effect of the WeChat app combined with pelvic floor muscle exercise (PFME) on urinary incontinence (UI) for patients treated with radical prostatectomy (RP). Patients and Methods. We retrospectively reviewed 112 patients who not only had done open RP or laparoscopic RP in our institution but also had sufficient data: preoperative information and more than one year of follow-up records. All the patients received instructions in correct pelvic floor muscle contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…This change in communication mode led to a significant decrease in urinary leakage at 1–3 months compared with PFME alone (24-h pad test (g): mean ± s.d. 254 ± 76 in the intervention group versus 293 ± 86 in the control group at 1 month, P < 0.05, and mean 76 ± 47 versus 98 ± 58 at 3 months, P < 0.05) 223 .…”
Section: Patient Motivation and Compliancementioning
confidence: 83%
“…This change in communication mode led to a significant decrease in urinary leakage at 1–3 months compared with PFME alone (24-h pad test (g): mean ± s.d. 254 ± 76 in the intervention group versus 293 ± 86 in the control group at 1 month, P < 0.05, and mean 76 ± 47 versus 98 ± 58 at 3 months, P < 0.05) 223 .…”
Section: Patient Motivation and Compliancementioning
confidence: 83%
“…16 As well, after 1 year of WeChat intervention, there was significantly improved self-reported continence in post-surgical prostate cancer patients, compared to the participants’ immediate post-surgical continence ( p < 0.001). 21 Statistically significant lower treatment discomfort scores were reported among breast cancer patients after a WeChat and telephone intervention period of 3 months, compared to a telephone control group. 25 In a 4 year follow up period of a randomized controlled trial, there was increased non-statistically significant survivorship values reported when comparing the WeChat intervention group to the telephone control group.…”
Section: Resultsmentioning
confidence: 86%
“…The number of consultation items has significantly increased over a short period, which may be related to the attitude toward the public's unknown and panic psychology at the early stage of the outbreak [11], which needed to be addressed by medical experts providing professional answers and psychological counseling. Multiple studies [12][13][14][15] have revealed that WeChat consultation services can deliver effective, convenient, and timely help to the general public.…”
Section: Discussionmentioning
confidence: 99%